Effect of different herbs on egg production in La Ying Hens - Walter Joseph Kulip (Universiti Malaysia Sabah, 2017)
Twenty-one week old of 96 hens were assigned to a 4 X 6 X 4 factorial arrangement as a completely randomized design with 4 treatments of 6 replicate for each treatment. Day Old Chick (DOC) raised in Poultry Research Facility, Faculty of Sustainable Agriculture, Univeristi Malaysia Sabah, to study the effect of different type of herbs {Turmeric-TR, Daun Kesum-DK, Bawang Dayak-BWD) on egg production performance of Bovan Brown chicken breeds. Egg performance may be depending on the dosage of substance used. Feed formulation nutrient analysis was done to study the content of feed. There is evidence that dietary plants affect the egg production which might be an interesting subject to the egg processing industry. It is concluded that the supplementation of layer diets with Turmeric, Daun Kesum, and Bawang Dayak herbs did not significantly affect parameters (P>0.05) at 1 % inclusion on the yd week of experiment.